2011
DOI: 10.3406/revec.2011.1608
|View full text |Cite
|
Sign up to set email alerts
|

An insight into diversity of the Balkan Peninsula bryophyte flora in the European background

Abstract: Aperçu de la diversité de la flore des bryophytes de la péninsule des Balkans dans le contexte européen. Les bryophytes de la péninsule Balkanique sont toujours très pauvrement connues et, au point de vue bryologique, l’Europe du Sud-Est demeure la région la moins prospectée en Europe. Le but de cette étude est d’évaluer l’état des connaissances sur la richesse de la diversité des bryophytes dans la péninsule Balkanique par rapport à l’Europe. Ainsi, la richesse spécifique (diversité alpha), la tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…120 liverworts (Marka et al 2018, Sabovljević & Natcheva 2006 were reported. Th e total number of bryophyte taxa has recently been increased considerably (to ca 585), and is already comparable to the species diversity of other countries in the Balkan Peninsula (Sabovljević et al 2011); this is due to a rise of interest and several collecting trips and publications during the last decade (e.g. Marka et al 2018, Marka 2014, van Zanten 2013, Papp et al 2010a.…”
Section: Introductionmentioning
confidence: 94%
“…120 liverworts (Marka et al 2018, Sabovljević & Natcheva 2006 were reported. Th e total number of bryophyte taxa has recently been increased considerably (to ca 585), and is already comparable to the species diversity of other countries in the Balkan Peninsula (Sabovljević et al 2011); this is due to a rise of interest and several collecting trips and publications during the last decade (e.g. Marka et al 2018, Marka 2014, van Zanten 2013, Papp et al 2010a.…”
Section: Introductionmentioning
confidence: 94%
“…Even in comparison to other European countries, Serbia has a rich bryophyte flora containing 118 liverworts (Sabovljević and Natcheva, 2006) and 555 moss species (Sabovljević et al, 2008(Sabovljević et al, , 2011. Bryophyte research, however, has received very little attention, and has been a secondary discipline within the botany of the country until the last decade (Sabovljević et al 2001;Sabovljević, 2004), when our work started and resulted in the expansion of known bryophytes by 25% (hepatics) and 15% (mosses), respectively (Papp et al, 2009).…”
Section: Introductionmentioning
confidence: 99%